Intramucosal carcinoma of the gastric antrum complicating Menetrier's disease. Issue 9 (September 1983) - Wood, M G; Bates, C; Brown, R C; Losowsky, M S
Abstract : A 48-year-old man presented with haematemesis and was found to have Menetrier's disease. Three and a half years later early gastric cancer was detected at routine follow-up endoscopy. This is the first report of the development of early gastric cancer during follow-up in a case of Menetrier's disease. It is probable that patients with Menetrier's disease are at increased risk of gastric cancer, and should have regular endoscopic follow-up with gastric biopsy.